Fluorinated porous organic frameworks for improved CO2 and CH4 capture. Issue 61 (10th July 2019) - Comotti, A.; Castiglioni, F.; Bracco, S.; Perego, J.; Pedrini, A.; Negroni, M.; Sozzani, P.
Abstract : Hyperpolarized 129 Xe NMR highlights open porosity of fluorinated organic frameworks which show CO2 and CH4 capture with high selectivity towards N2 . Abstract : A porous 3D selectively fluorinated framework (F-PAF1), robust yet flexible and with a surface area of 2050 m 2 g −1, was synthesised by condensation of an ad hoc prepared fluorinated tetraphenylmethane (TPM) monomer to ensure homogenously distributed C–F dipoles in the swellable architecture. Tetradentate TPM was also the comonomer for the reaction with fluorinated difunctional monomers to obtain frameworks (FMFs) with a controlled amount of regularly spaced reorientable C–F dipoles. The isosteric heat of adsorption of CO2 was increased by 53% by even moderate C–F dipole insertion, with respect to the non-fluorinated frameworks. CO2 /N2 selectivity was also increased up to a value of 50 for the difluoro-containing comonomer. Moreover, methane shows optimal interaction energies of 24 kJ mol −1 .